Plasma Methylmalonic Acid Concentration in Folic Acid–Supplemented Depressed Patients with Low or Marginal Vitamin B-12: A Randomized Trial. Issue 12 (11th September 2021) - Carter, Ben; Zenasni, Zohra; Moat, Stuart J; Hudson, Peter R; Russell, Ian T; McCaddon, Andrew; ,
ABSTRACT: Background: Individuals with low serum vitamin B-12 and high serum folate have higher plasma concentrations of methylmalonic acid (MMA). Whether folic acid (FA) causes an increase in MMA is not known. Objectives: We aimed to determine the impact of FA supplementation on plasma MMA concentration in people with low or marginal serum vitamin B-12. Methods: We conducted a multicenter double-blind placebo-controlled randomized trial of oral FA (5 mg/d for 12 wk) in middle-aged patients treated with antidepressant medication participating in the FoLATED (Folate Augmentation of Treatment—Evaluation for Depression) trial. Participants defined as having "low" serum vitamin B-12 (vitamin B-12 ≥150 and <220 ng/L) or "marginal" serum vitamin B-12 (vitamin B-12 ≥ 220 and <280 ng/L) were included. The primary outcome of this substudy was MMA at week 12. A mixed-effects linear regression was fitted and reported using the adjusted mean difference (aMD). Results: A total of 177 participants were included (85 randomly assigned to placebo and 92 to FA); the mean ± SD age was 46.2 ± 11.8 y, and 112 (63.3%) were female. The MMA analysis included 135 participants and the aMD was −0.01 (95% CI: −0.06, 0.04; P  = 0.71). Serum folate was measured on 166 participants and increased in the supplementation group; the aMD was 21.6 μg/L (95% CI: 8.13, 25.02 μg/L; P  < 0.001). A total of 117 participants were assessed for RBC folate, which also increased in the supplementation group; the aMD was 461 μg/L (95% CI: 387, 535 μg/L; P  < 0.001). Conclusions: Supplementation of FA leads to an increase of serum and RBC folate, but does not change plasma MMA concentration in individuals with serum vitamin B-12 between 150 and 280 ng/L. We cannot exclude effects in older people or those with serum vitamin B-12 <150 ng/L. Previously reported associations may arise from effects of impaired vitamin B-12 status on folate metabolism. This trial was registered at www.isrctn.com as ISRCTN37558856.